GUI system for enhancing blood vessels segmentation in digital fundus images / Ahmad Zikri Rozlan, Nor Syazwani Mohd Ali and Hadzli Hashim - Rozlan, Ahmad Zikri; Mohd Ali, Nor Syazwani; Hashim, Hadzli (2012)
An automated image processing system has the potential to aid ophthalmologist in diagnosing eye retinopathy diseases by presenting changes of retina features. One of the algorithms involved in the process is blood vessels segmentation. This paper proposes development of a Graphical User Interface (GUI) system that produces enhancement of blood vessels segmentation in digital fundus images. The system can help ophthalmologist in improving morphological procedures by observing significant features in the processed images for early diagnosis. The process of GUI creation is by using Qt Creator software while blood vessels segmentation methods utilize Canny and other morphology-based techniques. The outcome is a better processed image that can be the basis for further image enhancement so that eventually a diagnostic tool for diabetic retinopathy can be produced.